An integrated approach to the diffusion of technological innovation the non-manufacturing advanced robotics field - Sgobbi, Francesca
The author develops an evaluation model which can be used for 'embryonic technologies' and demonstrates its application to the technology of advanced robotics.
The search for new investment evaluation techniques is justified by the increasing gap between the current scenario and the technological and environmental conditions where the 'traditional' techniques have been developed. This is particularly true for 'embryonic technologies'-those technologies so innovative that the actual number of their operative applications is still negligible. It is important to evaluate the relevance of the technology since its embryonic stage springs from the need to assess its impact over society as a whole. A survey of economic literature underlines that neither traditional nor innovative techniques are able properly to evaluate embryonic technologies : beyond the need for historic data, they barely stress the role played by linkages between the expected benefits and the economic participants involved in determining the success of the technology. An evaluation model is thus developed which focuses on those elements. The way to build a set of indicators useful for assessing the potential of embryonic technology and monitoring its evolution is also depicted. An example related to an embryonic technology (advanced robotics) is discussed.
Keywords: Technological innovation; Robotics